Computer supported remote learning and gaming using Tele-Face Mouse system - Ahn, Sang Chul; Kim, Jin Hak; Kim, Hyoung-Gon (SPRINGER-VERLAG BERLIN, 2006)
This paper presents a new computer supported remote learning and gaming method using Tele-Face Mouse system. The Tele-Face Mouse system is being developed as a teleconference system. It converts simple desktop computers to a teleconference system. The main advantage of the Tele-Face Mouse system is that it enables people to share a computer screen as a working space, and to interact with it using mouse pointers that followed by user face videos. By presenting that it is also the key point in remote learning, this paper shows that the Tele-Face Mouse system can be effectively used in remote learning and gaming.